Acute Cordyceps militaris supplementation and elevated resting oxygen uptake with faster reaction times: A randomized crossover trial - Hamidreza Farzan; Maryam Koushkie Jahromi (PLoS ONE, 2026)
Background Cordyceps militaris (CM) demonstrates neuroprotective properties in chronic preclinical models, but its acute effects on cognitive and physiological parameters during exhaustive exercise remain uncharacterized in humans. Study design In a randomized, double-blind, placebo-controlled crossover trial with a 7-day washout, 12 recreationally active young men (mean age 21.6 ± 2.9 years, VO₂max: 38.6 ± 5.5 mL·kg ⁻ ¹·min ⁻ ¹) ingested 1 g of standardized CM extract or a cornstarch placebo 30 minutes before a maximal cycling test to exhaustion. Cognitive performance (Stroop reaction time and accuracy) and physiological measures (oxygen uptake, blood glucose, blood pressure, and heart rate) were assessed pre-exercise and 3 minutes’ post-exercise. Results Stroop reaction time exhibited a significant main effect of Condition (F(1,11) = 5.45, p = 0.040) and Time (F(1,11) = 16.37, p = 0.002), with faster responses overall in the CM condition. Both conditions improved from pre- to post-exercise (placebo: −148.92 ms; CM: −104.67 ms). The Condition × Time interaction was non-significant (F(1,11) = 1.01, p = 0.337). No between-group difference was observed at pre-exercise (p = 0.167), but CM produced faster reaction times at post-exercise (963.92 ± 84.99 ms vs. 1034.33 ± 84.16 ms; p = 0.042, d = 0.88). Accuracy remained near-ceiling (>99%) with no condition differences. CM elevated resting VO₂ (0.37 vs. 0.24 L/min; p = 0.022) without altering peak exercise VO₂ (p = 0.490). No significant Condition effects or interactions were observed for blood glucose, blood pressure, or heart rate (all p > 0.05). Conclusion Acute CM supplementation improved post-exercise reaction time and elevated resting oxygen uptake, but did not alter the magnitude of exercise-induced changes in cognitive or physiological parameters. This suggests CM exerts an acute cognitive benefit independent of exercise modulation.